Identification of mitochondrial related gene characteristics and potential molecular mechanism of acute otitis media - Zi, Dingjing; Ren, Xiaoyong (Frontiers in Molecular Biosciences, 2025)
BackgroundAcute otitis media (AOM) is a prevalent pediatric infection worldwide, with mitochondrial dysfunction and immune responses implicated in its pathogenesis. However, the precise mechanisms remain elusive.MethodsMitochondrial-related genes were extracted from Spn-AOM and NTHi-AOM datasets in the Gene Expression Omnibus (GEO). Differentially expressed mitochondrial genes (MitoDEGs) were identified and analyzed through functional enrichment analysis. Key MitoDEGs strongly linked to AOM were determined using least absolute shrinkage and selection operator (LASSO) and random forest (RF) models. Immune cell infiltration patterns were evaluated via the Cibersort algorithm, and associations between hub MitoDEGs and immune cells were examined. A regulatory network was established to elucidate gene regulation, and qRT-PCR validation was performed in C57BL/6 mice.ResultsWe identified 18 MitoDEGs in Spn-AOM and 14 in NTHi-AOM. Functional enrichment analysis highlighted their involvement in mitochondrial processes, peroxisomal activity, cell cycle control, and amino acid metabolism. LASSO and RF analyses pinpointed FAM110B, LIG1, and PDK1 as key genes. Immune infiltration analysis demonstrated significant associations between these genes and immune cell composition. TF-miRNA-mRNA network predictions suggested potential regulatory mechanisms.ConclusionThis study reveals mitochondrial gene expression alterations in AOM, identifying FAM110B, LIG1, and PDK1 as critical genes associated with immune cell infiltration. These findings provide insights into the mitochondrial-immune interplay in AOM pathogenesis.